DNA synthesis at individual replication forks requires the essential initiation factor Cdc45p - Tercero, José Antonio (Oxford University Press, 2000)
Cdc45p assembles at replication origins before initia tion and is required for origin firing in Saccharomyces cerevisiae. A heat-inducible cdc45 degron mutant was constructed that promotes rapid degradation of Cdc45p at the restrictive temperature. Consistent with a role in initiation, loss of Cdc45p in G(1) prevents all detectable DNA replication without preventing subsequent entry into mitosis. Loss of Cdc45p activity during S-phase blocks S-phase completion but not activation of replication checkpoints. Using density substitution, we show that after allowing replication fork establishment, Cdc45p inactivation prevents the subsequent progression of individual replication forks. This provides the first direct functional evidence that Cdc45p plays an essential role during elongation. Thus, like the large T antigen in SV40 replication, Cdc45p plays a central role in both initiation and elongation phases of chromosomal DNA replication.